Necessidades em saúde na voz de usuários da Estratégia de Saúde da Família - Elaine Miguel Delvivo Farão (2020)
This is a qualitative research aimed at preparing a theorization about the meaning of health needs for users of the Family Health Strategy (FHS). The theoretical framework adopted was the symbolic interactionism, while the methodological one was the Grounded Theory (GT). We interviewed twenty-three users of Primary Health Care (PHC) in the town of Coxim – MS, from February to November 2018. The interviews were recorded, transcribed and analyzed, where the analysis was concomitant with the data collection. The interviews lasted an average of one hour. Firstly, the participants were randomly selected; however, as proposed by GT, during the analysis of the data, sample groups were formed, with the purpose of expanding the variability of the conceptions about the studied phenomenon. The data were analyzed using open, axial and selective coding. The analysis highlighted four categories: the first entitled “The Very Needs of Interactions in Everyday Life”. The second and third categories were, respectively, called: “Relationship with the Transcendent” as a support in the care of Health Needs and “The Affected Needs – when the physical state is visibly worsened”. The fourth category was called “Health Services: Responses to the Needs Not Solved by Self-Care”. The categories were prepared in a related and interconnected way, thereby enabling the development of the central category, which consists in the Theory of this study: The Health Needs: trajectories in search of living with quality in everyday existence. Health Needs take place in everyday life, involving the personal relationships: With You – Self, with people – social relationships and with the Space where you live. Moreover, the Needs are constituted of the “Relationship with the Transcendent”, which is based on the Faith of the human being in God or in Something Superior, with different denominations for the participants. This Faith is a resource for the care of itself and of the other in social relationships. In addition, it also works as a Support for Dealing with the Problems experienced in everyday life. When the Health Needs are affected, usually translated into pain or symptoms of illness, people seek previously known treatments, such as medications and teas. If the limitations for the performance of daily activities remain, they look towards the health service as a last resource to supply their needs. The care offered in the health service is geared towards illness, either treatment or prevention. It is revealed that the very needs of interactions in everyday life are not considered by users as demands that require care in health services. Accordingly, as they distance themselves from biological demands, they are not taken care of by health professionals in the context of PHC and reflect that comprehensive care, health promotion and the enhancement of healthy ways of living still remain a challenge within the scope of the Brazilian Unified Health System (SUS, as per its Portuguese acronym). Nevertheless, the theoretical framework developed proposes that the meaning of Health Needs may be translated by the complexity of the personal relationships with the aim at achieving health throughout life. Thus, it involves and is the result of the interactions established with the Self, the Other and the Environment in Society, thereby being related to the very way of being and existing in Everyday Life.